"Good versus Evil" after the Cold War: Kosovo and the Moralisation of War Reporting - Hammond, Philip (Javnost-The Public, 2000)
Focusing on coverage of the 1999 Kosovo conflict, this paper examines the trend towards framing contemporary wars and interventions in moral terms, and highlights the threat this poses to accurate and informative reporting. Kosovo represented the latest stage in a process of re-framing international relations in the post-Cold War era, and drew on three different news frames developed in earlier Western reporting of Yugoslavia during the 1990s, which portrayed the break-up of the country as a continuation of the Cold War, as the product of "ethnic" hatred, and as a repeat of the Holocaust. The significance of today's moralised framework is that the "moral imperative" to intervene can override all other considerations, including national sovereignty and international law. In practice the supposedly "universal" discourse of human rights and humanitarianism becomes an apology for an elitist division of the world into (morally) superior and inferior peoples and states. Journalists have played an important and active role in developing and disseminating influential interpretations of the post-Cold War world. The rhetoric of "Good versus Evil" deployed by Nato leaders in Kosovo drew on explanatory frameworks which liberal journalists, commentators and intellectuals had helped to elaborate during the Bosnian conflict.